Custom made ocular prosthesis: A case report - Devkota, D; Mathema, SRB (Journal of Nepalese Prosthodontic Society, 2021)
Physical defects that compromise appearance or function, which prevent an individual from leading a normal life, usually prompt the individual to seek treatment that will reinstate acceptable normalcy. The loss of an eye impairs the patient’s visual function, yet also results in a noticeable deformity. Prosthesis should be provided as soon as possible to raise the spirits and ease the mind of the afflicted. An ocular prosthesis is a maxillofacial prosthesis that artificially replaces an eye missing as a result of trauma, surgery, or congenital absence. A custom ocular prosthesis has advantage of close adaptation to the tissue bed, provides maximum comfort and restores full physiological function to the accessory organs of the eye.